Mediation and cultural legitimacy: the imprint of social networks - Cordón, José-Antonio; Alonso-Arévalo, Julio (Anuario ThinkEPI, 2012)
Social networks are emerging as a core element in professional and literary accreditation systems, shaping not only a new form of opinion generation, but also an information structure that organizes the rules of the medium. Their organization, syntax and internal rules so determine the forms of participation that whatever doesn´t fit with them simply cannot exist as a cultural product.